2020
DOI: 10.1051/shsconf/20208601027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Profitability Ratio, Liquidity Ratio, Leverage Ratio, and Company Size on Sukuk Rating Corporation During 2014-2017 Periods

Abstract: The purpose of this study was to destermine the effect of profitability ratios, liquidity ratios, leverage ratios, and company size toward sukuk ratings in Indonesia during 2014-2017. The independent variables in this study is profitability ratios, liquidity ratios, leverage ratios, and company size, while the dependent variable is sukuk rating. The object of this study is Corporations for the period 2014-2017, this study used 78 samples. The technique sampling method in this study used purposive sampling. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Though this study did not manage to support signaling theory from the perspective of profitability, several prior studies found similar findings. Among those studies were Sihombing and Rachmawati (2015), Kustiyaningrum, Nurani & Wijaya (2017), and Suratmi & Rahmawati (2020).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Though this study did not manage to support signaling theory from the perspective of profitability, several prior studies found similar findings. Among those studies were Sihombing and Rachmawati (2015), Kustiyaningrum, Nurani & Wijaya (2017), and Suratmi & Rahmawati (2020).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Elhaj et al (2015), Astuti (2017), Pebruari (2017), Haraqi and Ningsih (2018), Borhan and Ahmad (2018), Rofi (2020) and Rukmana and Laila (2021) reported that profitability has a positive impact on sukuk rating. Only a few previous studies found that profitability has no effect on sukuk rating such as Sihombing and Rachmawati (2015), Kustiyaningrum, Nurani & Wijaya (2017), and Suratmi & Rahmawati (2020), and (Muarif, Ibrahim, & Amri, 2021).…”
Section: Empirical Review On the Determinants Of Sukuk Ratingmentioning
confidence: 97%
See 3 more Smart Citations